2022
DOI: 10.3390/membranes12090857
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Sorption and Transport of Gases in Polymeric Membranes across Different Scales: A Review

Abstract: Professor Giulio C. Sarti has provided outstanding contributions to the modelling of fluid sorption and transport in polymeric materials, with a special eye on industrial applications such as membrane separation, due to his Chemical Engineering background. He was the co-creator of innovative theories such as the Non-Equilibrium Theory for Glassy Polymers (NET-GP), a flexible tool to estimate the solubility of pure and mixed fluids in a wide range of polymers, and of the Standard Transport Model (STM) for estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 402 publications
0
20
0
Order By: Relevance
“…When a specific force field is used to describe polymer behaviour, it is essential to confirm its capability to correctly reproduce volumetric and energetic parameters before predictions of the sorption and transport properties of different gases can be undertaken [ 20 , 21 , 22 , 23 ]. Figure 3 shows the snapshots of the equilibrated structures for two homopolymers as an example.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When a specific force field is used to describe polymer behaviour, it is essential to confirm its capability to correctly reproduce volumetric and energetic parameters before predictions of the sorption and transport properties of different gases can be undertaken [ 20 , 21 , 22 , 23 ]. Figure 3 shows the snapshots of the equilibrated structures for two homopolymers as an example.…”
Section: Resultsmentioning
confidence: 99%
“…The last 5 ns of the trajectories on 4 copolymers, namely PHBV0, PHBV8, PHBV60, and PHBV100 systems, were used to perform the Widom test particle insertions [ 48 ] in order to calculate the excess chemical potential of CO 2 and CH 4 at infinite dilution, as described elsewhere [ 23 , 49 ], and from that the solubility. Although several methods exist to simulate the solubility in polymers, for which we address the reader to competent and extended reviews [ 20 , 50 ], the Widom insertion method is deemed optimal for the low-concentration sorption of small molecules, as is the case inspected here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics that these polymers must fulfil to have a good performance are, above all, a high permeate flux and a high selectivity. In addition, they must also have high mechanical strength, high temperature resistance, chemical stability, and easy processability [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most available models are parametric and differ in the approximations used in their derivation, scope of applicability, and predictive capabilities. A comprehensive review of the parametric models can be found elswhere 12 . The advantages of models of this type are the ease of implementation, a small number of clearly interpreted parameters, and the possibility to use tabulated parameters due to a large amount of accumulated literature data.…”
Section: Introductionmentioning
confidence: 99%